Existence and Uniqueness of Solution of Stochastic Dynamic Systems with Markov Switching and Concentration Points - Taras Lukashiv; Igor Malyk (International Journal of Differential Equations)
In this article the problem of existence and uniqueness of solutions of stochastic differential equations with jumps and concentration points are solved. The theoretical results are illustrated by one example.